2021
DOI: 10.3390/w13131817
|View full text |Cite
|
Sign up to set email alerts
|

Pilot and Field Studies of Modular Bioretention Tree System with Talipariti tiliaceum and Engineered Soil Filter Media in the Tropics

Abstract: Stormwater runoff management is challenging in a highly urbanised tropical environment due to the unique space constraints and tropical climate conditions. A modular bioretention tree (MBT) with a small footprint and a reduced on-site installation time was explored for application in a tropical environment. Tree species used in the pilot studies were Talipariti tiliaceum (TT1) and Sterculia macrophylla (TT2). Both of the MBTs could effectively remove total suspended solids (TSS), total phosphorus (TP), zinc, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…The majority of experimental studies characterizing stormwater nutrient retention considered trees as part of NBS installations. These typically involved controlling stormwater inputs and soil hydrological conditions in mesocosms, either representing modular (Lim et al., 2021) or street‐scale bioretention systems (Denman et al., 2016; Tirpak, Hathaway, & Franklin, 2019) including those initiatives forming part of suspended pavement installations (Page et al., 2015; Tirpak et al., 2019b). The studies largely showed NBS to be beneficial, although those of Tirpak, Hathway & Franklin (2019), Tirpak, Hathway, Franklin, et al.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of experimental studies characterizing stormwater nutrient retention considered trees as part of NBS installations. These typically involved controlling stormwater inputs and soil hydrological conditions in mesocosms, either representing modular (Lim et al., 2021) or street‐scale bioretention systems (Denman et al., 2016; Tirpak, Hathaway, & Franklin, 2019) including those initiatives forming part of suspended pavement installations (Page et al., 2015; Tirpak et al., 2019b). The studies largely showed NBS to be beneficial, although those of Tirpak, Hathway & Franklin (2019), Tirpak, Hathway, Franklin, et al.…”
Section: Resultsmentioning
confidence: 99%
“…When comparing with other field studies in Singapore, similar information was obtained. Lim et al [38] observed poor pollutant removal efficiency for a modular bioretention tree system due to low influent runoff pollutant concentration, which may be caused by the high frequency and seasonal severity of storm events. Compared with another ABCWDF by Ong et al [19], the effluent concentrations were slightly lower in that study.…”
Section: Discussionmentioning
confidence: 99%
“…FB7 generally performed well in TSS removal with the average effluent TSS EMCs similar to the treatment objectives of 10.0 mg/L as stipulated in the ABC Waters design guidelines. However, if the system is assessed based on the percentage removal efficiency, poor efficiency (−34%) was obtained due to the low influent TSS EMCs [38]. Various field studies in the temperate region reported a similar range of bioretention effluent TSS concentration [39,40], but positive removal efficiency due to higher influent TSS concentration.…”
Section: Natural Storm Eventsmentioning
confidence: 99%
“…regardless of the research design and setup (Barron et al 2020;Blecken et al 2010;Bratieres et al 2008;Fowdar et al 2017;Hatt et al 2009;Hsieh and Davis 2005;Lim et al 2021;Søberg et al 2020).…”
Section: Tss Concentrationmentioning
confidence: 99%